Hydrostatic extrusion-drawing of fine wire - Cheung, John S. T. (2008)
Hydrostatic extrusion is a possible alternative method of producing fine wires. This report describes mainly the experimental machine that has been design and built at NTI to test this process. The machine is designed for semi-continuous extrusion at a very high pressure of 960 MPa (9500 bars). The 25 mm diameter pressure chamber has a shrink-fit duplex construction. Pressure is generated throught two stages of intensification from normal shop air.